Evaluasi Program Rehabilitasi Sosial Rumah Tidak Layak Huni di Desa Tanjung Lipat Kabupaten Lingga - Riau Sujarwani; Suhandri (STISIPOL Raja Haji, 2021)
One of the development problems is poverty, poverty is marked by the inability to meet needs, one of which is housing needs, the need for decent housing is a concern for the central government and local governments. In this case, Lingga Regency, Riau Islands Province, received assistance to rehabilitate 80 uninhabitable housing units from the Ministry of Social Affairs (Kemensos) through the Social Rehabilitation Program for Uninhabitable Houses (RS-RUTILAHU). In implementing this program, the problems that arise in the community in Tanjung Fold Village, Bakung Serumpun Sub-district, Lingga Regency, namely: the community does not realize that the RS-RUTILAHU program only wants to ease the burden on the community in building houses that are livable, and the construction of houses is not on time. has been determined, then there are also recipients who do not deserve assistance but receive assistance. The purpose of this study was to evaluate the Social Rehabilitation Assistance Program for Uninhabitable Houses in Tanjung Fold Village, Lingga Regency. This research is descriptive qualitative. The population in this study is the community element as the main recipient of the Social Rehabilitation Program for Uninhabitable Homes in Tanjung Fold Village as many as 10 units as well as Key Informants Assisting recipients of assistance, Tanjung Fold Village Head, and employees at the Lingga Regency Social Service. The sampling technique is the purposive sampling technique. The data used are primary and secondary data. Data collection techniques using observation, and interviews. The data analysis technique is qualitative data analysis. The results of this study are that the Social Rehabilitation Program for Uninhabitable Houses (RUTILAHU) in the village of Tanjung Fold, Lingga Regency has achieved its main goal, namely to facilitate the poor for housing needs that are livable, but not maximized. Suggestions that can be given are monitoring and supervision in the implementation of assistant duties which must also be carried out by the Tanjung Fold Village which is responsible to the receiving community and also the Lingga Regency Social and Labor Agency.